Network meta-analysis for indirect comparison of lanadelumab and berotralstat for the treatment of hereditary angioedema - Maureen Watt; Mia Malmenas; Dorothy Romanus; Katrin Haeussler (Becaris Publishing Limited, 2023)
Aim: With no head-to-head studies comparing the effectiveness of lanadelumab and berotralstat for prevention of hereditary angioedema (HAE) attacks, this networkmeta-analysis (NMA) aimed to indirectly compare the effectiveness of these treatments. Materials & methods: The NMA, using the published data from Phase III trials, was performed using a frequentist weighted regression-based approach following Ru¨ cker et al. Efficacy outcomes of interest were HAE attack rate per 28 days and ≥90% reduction in monthly HAE attacks. Results & conclusion: In this NMA, lanadelumab 300 mg administered every 2 weeks or every 4 weeks was associated with statistically significantly higher effectiveness versus berotralstat 150 mg once daily (q.d.) or 110 mg q.d. for both efficacy outcomes assessed.